The Utilization of the PlantNet Application in Biology Learning and Its Impact on Senior High School Students’ Learning Retention - Sepriana,; Chastanti, Ika; Nazliah, Rahmi (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to determine students’ retention levels before and after the implementation of the PlantNet application and to analyze the effect of the PlantNet application on students’ retention in biology learning at SMA Negeri 1 Aek Natas. The study employed a quantitative approach with descriptive analysis. The research participants consisted of 61 tenth-grade students, including 31 students from class X2 and 30 students from class X3. The research instruments included a questionnaire measuring students’ perceptions of the use of the PlantNet application and a retention test designed to assess short-term retention, long-term retention, and conceptual understanding. The collected data were analyzed using percentage analysis to determine the achievement level of each indicator.The results indicated that the use of the PlantNet application was categorized as very good, with the ease-of-use indicator reaching 91.7% and the usefulness in learning indicator reaching 88.8%. Regarding student retention, short-term retention reached 83.4%, long-term retention reached 84.2%, and conceptual understanding reached 84.6%, all of which were classified as good. These findings suggest that the PlantNet application is not only easy to use and beneficial for biology learning but also contributes to strengthening students’ memory retention and improving their conceptual understanding of the learning material. Therefore, the integration of the PlantNet application has strong potential to serve as an effective instructional medium for enhancing students’ retention in biology learning.